Rising Amidst Turbulence: A Phenomenological Exploration of Online Sellers’ Lived Experiences During the COVID-19 Pandemic - Argabioso, Nierene M.; Orencia, Abrian Joy B. (Future Science / FSH-PH Publications, 2023)
Environmental turbulence manifested by uncertainties and complexities has been extensively studied recently, especially that the 21st century is marked by significant phenomena like the shift to Digitalization and the COVID-19 Pandemic. With the rapid growth of e-commerce in the Philippines, increasing interest in research about it is also observed, but only few studies focused on online sellers. Being part of the MSMEs, which comprises 99.17% of the industry, it is now high time to explore the lived experiences of online sellers during the COVID 19 Pandemic. An interpretative phenomenological analysis based on hermeneutics was used to make sense of the responses of six participants from the Greater Metro Manila Area, gathered from semi- structured interviews based on Moustakas’ data gathering and analysis methods. There were eleven themes collected, and from these themes the textural and structural description were synthesized through the universal structure. Reciprocity of exchange was mainly the reason in establishing their online businesses while personal challenges were mostly what have been experienced. On how they experienced the phenomenon, most responses manifested new strategies of resilience, and how they see the future of their business is focused more on their envisioned future.